A classification of primary care streaming pathways in UK emergency departments: Findings from a multi-methods study comprising cross-sectional survey; site visits with observations, semi-structured and informal interviews. (May 2021) - Edwards, Michelle; Cooper, Alison; Hughes, Thomas; Davies, Freya; Sherlock, Rebecca; Anderson, Pippa; Evans, Bridie; Carson-Stevens, Andrew; Cooke, Matthew; Dale, Jeremy; Hibbert, Peter; Harrington, Barbara; et al.
Abstract: Background: Variation in initial assessment methods at emergency departments in with primary care service models and a conflated terminology causes difficulties in assessing relative performance, improving quality or gathering evidence about safety and clinical effectiveness. We aim to describe and classify streaming pathways in emergency departments in different models of emergency department primary care services in England and Wales. Methods: We used a multi-stage method, including an online survey completed by 77 emergency departments across England & Wales, interviews with 21 clinical leads, and in-depth case studies of 13 emergency departments. All qualitative data were triangulated and analysed using a framework approach. Results: Common emergency department pathways to primary care services were: front door streaming; streaming inside the emergency department; or primary care staff selecting patients. Pathways were also in place to redirect patients with non-urgent primary care problems to community primary care services. Streaming and redirection pathways were often adapted, with variation in protocols based on local circumstances. Conclusion: Clinical leads should consider which pathway(s) best suit their local context. Consistency of terminology used to describe pathways between emergency departments and primary care services is necessary for performance measurement, quality improvement and rigorous future multi-site evaluative and descriptive research.